Nanocomposite films with silver nanoparticles synthesized in situ: Effect of corn starch content - Ortega, Florencia (2019)
The aim of this work was to analyze the effect of native corn starch content (1, 3 and 5% w/v) on the development of nanocomposite films with 143 ppm silver nanoparticles (AgNPs) synthesized in situ. The tested concentrations allowed synthesizing AgNPs in situ and suspensions maintained their filmogenic capacity, regardless the starch content. The characteristics of AgNPs were studied by spectrophotometric techniques, highresolution transmission electron microscopy (HR-TEM) and zeta potential measurement, finding they are spherical with diameters between 19.9 and 13.4 nm and negatively charged. Films containing 1% starch, were difficult to handle coinciding with the mechanical profile obtained, which corresponds to a slightly ductile material. Nanocomposite films with 5% starch showed improved mechanical and barrier properties due to the increase of starch content, but they did not evidence a matrix reinforcement by the AgNPs incorporation. Furthermore, films containing 3% starch show the optimal mechanical and barrier properties, attributed to the reinforcement of AgNPs. Regarding the antimicrobial capacity, all nanocomposite films inhibited microorganisms’ growth. Thus, considering the obtained results nanocomposite films formulated with 3% starch were selected as the most suitable option for their application as food packaging.